Piyesta sa hardin ni lola Benita Fiesta in lola Benita's garden - Evasco, Eugene Y. (Chikiting books, 2014)
"Fiesta is the most colorful tradition of the Filipinos. People cook delicious meals for the visitors. Oftentimes, the food may be too salty, sweet, or fatty. This book highlights the value of eating right to have a healthy body. It is a delightful srory that presents the fresh and colorful banquet of lola Benita whose dishes come directly from the garden."